Educational Service Strategy in Increasing Public Interest in Madrasahs and Integrated Islamic Schools - Fauzi, Anis; Misbayani, Misbayani; Rohmiyati, Yuli (Acta Pedagogia Asiana, 2026)
Public interest in integrated Islamic madrasahs and schools is growing, yet challenges remain in delivering comprehensive and effective educational services. This study aimed to explore the forms of educational services developed in madrasahs and integrated Islamic schools, as well as the involvement of teachers, educational personnel, and parents in enhancing service quality. A qualitative descriptive approach was employed, using in-depth interviews, observations, and documentation at four research sites in Serang City, Indonesia. Participants included school principals, teachers, administrative staff, and parents. The results indicated that suitable educational services in madrasahs comprised core subject learning, extracurricular activities, talent development, and library services. Additional facilities included science laboratories, counseling rooms, places of worship, school cooperatives, canteens, and multimedia rooms. In integrated Islamic junior high schools, services also involved dormitory management, health programs, and auxiliary services such as laundry and sewing. Teacher councils and educational personnel actively supported these services, while parental involvement further enhanced service quality. Limitations included restricted land for sports facilities and the need for improved public awareness of new services. In conclusion, integrated Islamic schools that implement comprehensive educational strategies attract greater public interest and foster holistic student development. Future research should investigate the long-term impact of these services on academic performance, character formation, and community engagement, as well as strategies to optimize limited resources and expand access to high-quality educational services.